Flash technology-based self-assembly in nanoformulation: Fabrication to biomedical applications. (January 2021) - Hu, Hanze; Yang, Chao; Li, Mingqiang; Shao, Dan; Mao, Hai-Quan; Leong, Kam W.
Graphical abstract: Abstract: Advances in nanoformulation have driven progress in biomedicine by producing nanoscale tools for biosensing, imaging, and drug delivery. Flash-based technology, the combination of rapid mixing technique with the self-assembly of macromolecules, is a new engine for the translational nanomedicine. Here, we review the state-of-the-art in flash-based self-assembly including theoretical and experimental principles, mixing device design, and applications. We highlight the fields of flash nanocomplexation (FNC) and flash nanoprecipitation (FNP), with an emphasis on biomedical applications of FNC, and discuss challenges and future directions for flash-based nanoformulation in biomedicine.